The Application of Iron (Fe) from Bay Leaves (Syzgium Polyanthum) in Food Flavoring Powder Formula - Jumiono, Aji; Barqin, Gesa Aldin; Widowati, Sri; Zhafarinnadia, Moura (Indonesian Journal of Applied Research (IJAR), 2024)
Anemia caused by iron deficiency is still a nutritional problem in Indonesia. New methods are needed to help increase blood levels of iron by utilizing the habit of people consuming and processing food. Bay leaves (Syzgium polyanthum) offer a potential solution to Indonesia's iron-deficiency anemia issue by utilizing common food consumption habits This research method was a quantitative experiment by finding the best ratio of comparison of the encapsulation leaf extract formula in bay leaves powder and conducted a test of the receipt of the powder formula. The best formula ratio in making powder found in this research was a formula with 4 gr bay leaf extract and seasoning ingredients (10 gr seaweed, 10 gr fried onion, 7 gr white sesame, 5 gr oyster mushrooms, 5 gr sugar, 2 gr salt, 1 gr powder garlic, sesame oil 15 ml, and pepper 0.2 gr. The formula has an iron level (Fe) of 3.2 mg, equivalent to 24.2% RDA.